2015
DOI: 10.1142/s0217732315501588
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of universes with the initial and final de Sitter eras

Abstract: Our aim is studying the thermodynamics of cosmological models including initial and final de-Sitter eras. For this propose, bearing Cai-Kim temperature in mind, we investigate the thermodynamic properties of a dark energy candidate with variable energy density, and show that the state parameter of this dark energy candidate should obey the ωD = −1 constraint, whiles there is no interaction between the fluids filled the universe, and the universe is not in the de-Sitter eras. Additionally, based on thermal fluc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 112 publications
(280 reference statements)
4
20
0
Order By: Relevance
“…Our study shows that, in quasi-topological gravity theory, a geometrical fluid with energy density ρ e and pressure p e , independent of its nature, affects the apparent horizon entropy as S A = A 4 − 2πnΩ n Hr n+1 A (ρ e + p e )dt, (58) which is in full agreement with other studies [28][29][30][31][32][33][34][35][36]. Since such correction in quasitopological gravity has geometrical nature, it is indeed inevitable.…”
Section: Second Law Of Thermodynamicssupporting
confidence: 90%
“…Our study shows that, in quasi-topological gravity theory, a geometrical fluid with energy density ρ e and pressure p e , independent of its nature, affects the apparent horizon entropy as S A = A 4 − 2πnΩ n Hr n+1 A (ρ e + p e )dt, (58) which is in full agreement with other studies [28][29][30][31][32][33][34][35][36]. Since such correction in quasitopological gravity has geometrical nature, it is indeed inevitable.…”
Section: Second Law Of Thermodynamicssupporting
confidence: 90%
“…Moreover, It is shown that the ultimate de-Sitter spacetime is in accordance with the thermodynamic equilibrium conditions, and therefore the cosmos may serve its final stage [38]. In this model, the state parameter of the vacuum energy satisfies the ω D = −1 condition, and thus the vacuum energy decays into the other fields confined to the apparent horizon of the FRW universe [36,39]. It is worthwhile to mention here that the decay of vacuum into the other fields is due to a mutual interaction between the cosmos sectors leading to leave thermal fluctuations into the cosmos in this model [39].…”
Section: Introductionmentioning
confidence: 91%
“…In continue, Mitra et al extended their hypothesis to other different gravity theories [78]. Moreover, it is also shown that a gravitationally induced particle production process as the DE candidate may change the horizon entropy [39]. Bearing the Lovelock theory in mind, some authors used the T dS A = AΨ − AΨ DE relation to get the entropy of the apparent horizon in cosmological setup [65].…”
Section: Horizon Entropy and The Unified First Law Of Thermodynamicsmentioning
confidence: 99%
See 2 more Smart Citations